The effects of tourism on the subjective well-being of the residents of Cappadocia - Ata, Selenay. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
World Heritage Sites represent an important attraction for prospective visitors to a destination. Although tourism significantly contributes to both national and local economies, it is of paramount importance to residents of destinations, whose lives are influenced by the prevalence of tourism activity to a great extent. Guided by previous research focusing on tourism’s effect on resident well-being, this study aims to investigate the relationship between subjective well-being of the residents and their perceptions of tourism and conservation in Göreme National Park and the Rock Sites of Cappadocia. This descriptive research uses a quantitative approach, in which a survey instrument consisting of a happiness index and questions on tourism and conservation measures was administered to 178 residents in Cappadocia using a convenience sampling approach. Study findings demonstrate that positive perceptions of tourism and conservation reinforce community well-being in Cappadocia. These results’ implications for future research and policy-makers are discussed.
Keywords: Tourism -- Cappadocia (Turkey)